Non-stoichiometric carbamazepine cocrystal hydrates of 3, 4-/3, 5-dihydroxybenzoic acids: coformer–water exchange. Issue 26 (15th March 2023) - Rajbongshi, Trishna; Sarmah, Kashyap Kumar; Das, Susobhan; Deka, Poonam; Saha, Arijit; Saha, Binoy K.; Puschmann, Horst; Reddy, C. Malla; Thakuria, Ranjit
Abstract : A unique set of carbamazepine (CBZ) non-stoichiometric cocrystal hydrates with 34/35DHBA have been synthesized which are facilitated by their isostructural nature with the CBZ dihydrate, resulting in coformer–water exchange (molecular alloy). Abstract : The cocrystallisation of carbamazepine (CBZ) with 3, 4-/3, 5-dihydroxybenzoic acids (34/35DHBA) with different stoichiometries formed molecular alloys, exchanging a water molecule, in their isostructural CBZ dihydrate form. Furthermore, we show a correlation between the mechanical properties of the CBZ–DHBA cocrystals with the amount of coformer present.